Application of Safety Riding on The Highway in The Perspective of Road Transportation Traffic Law - Mahadewi, Kadek Julia (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
The high number of accidents on the highway every year results in the government taking policies in carrying out legal protection for the public in driving on the highway. This is aimed at the Government to make efforts to estimate the number of accidents that result in the loss of a person's life. The government by using the Safety Riding method in driving on the highway hopes to reduce the number of accidents that arise in the community by paying attention to completeness and safety in traffic on the highway. The problem that arises How is the implementation of safety riding carried out by the government in relation to the UULAJ?. The purpose of this journal is so that the public has awareness carried out by the community, especially the younger generation, can have awareness of driving on the highway by remembering the importance of safety for themselves and others and a sense of safety and comfort when driving. The use of Safety Riding is inseparable from the role of the Government, Companies and the community in forming synergy in efforts to save traffic. The implementation of Safety Riding is present in the community to prevent the number of accidents so that the UULLAJ is a suggestion for legal protection in the community.